Thermodynamic Effects in the Tests on Dynamic Elongation of Polymer Composites - R. Gieleta; S. Ochelski (Engineering Transactions, 1993)
A method and results of dynamic tensile tests applied to an orthotropic polymer composite are described. Its mechanical properties are dependent on both the temperature and the strain rates. On the basis of experiments, the increments of the potentials of internal energy, free energy, enthalpy and free enthalpy are determined. The results are planned to, be used to formulate an energy strength criterion for a fibrous composite.